CIM-2-mod: A CIM to modelica mapping and model-2-model transformation engine - Francisco J. Gómez; Luigi Vanfretti; Miguel Aguilera; Svein H. Olsen (SoftwareX, 2019)
New requirement on power systems analysis tools consider information exchange for both steady-state and system dynamics information. New European regulations on information exchange power system dynamic simulations now require coordinating TSOs operations under different scenarios, some of which require to assess the dynamic behavior of power systems under a vast array of contingencies. As a mean to comply with these regulations and to advance the state-of-the-art, this work describes the software architecture of a Model-To-Model (M2M) transformation tool to create power system dynamic models using Modelica components by linking it to data from the Common Information Model (CIM). This software architecture is conceived to combine the CIM standard language with the Modelica standardized language, and to provide a Free/Libre Open Source Software (FLOSS) CIM-compliant unambiguous power system modeling solution considering both steady-state and dynamic model representations of the electrical grid. Keywords: Common information model, CIM, Model transformation, Information modeling, Modelica, OpenIPSL, Electrical power grid, Power system modeling, Power system dynamics, Power system simulation